UJI TOKSISITAS EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) MENGGUNAKAN METODE BRINE SHRIMP LETHALITY TESt (BSLT) PADA LARVA UDANG (Artemia salina Leach - Sitti Rahimah Rachman; Fadillah Maryam; Bertha Ayu Limbong (STIFA Makassar, 2019)
Brine Shrimp Lethality Test (BSLT) is one of the initial screening methods for testing cytotoxic compounds. Previous studies have scientifically proven that Averrhoa bilimbi L leaves have antioxidant effects so that the basis of the aim of this study is to determine the toxicity effects of ethanol extracts of starfruit starfruit shrimp (Artemia salina L.) using the BSLT method. Testing was done using several variations of concentration, namely 10 μg / mL, 250 μg / mL, 500 μg / mL, 750 μg / mL, and 1000 μg / mL. Based on observations and analysis of data obtained that the ethanol extract of Averrhoa bilimbi L leaves gives a moderate toxic effect with LC50 value of 367,282 ± 33.81 µg / mL.